Environmental Knowledge, Awareness, Attitude Toward Purchase Intention, Mediated by Infrastructure Readiness & Price Affordability of Electric Vehicle (EV): Case in Indonesia - Ramadhan, Naufalian; Nurdayadi, Nurdayadi; Alfiandri, Alfiandri (Jurnal Administrasi Bisnis, 2024)
The study investigates the impact of electric vehicle (EV) technology on Indonesia's automotive industry and economy, emphasizing EVs' role in emission reduction. Factors affecting EV uptake, including purchasing behavior and environmental awareness, are analyzed, contributing to the theory of planned behavior. Data from 136 respondents were collected through surveys, revealing positive correlations between environmental awareness, knowledge, attitude, and purchase intent. Price affordability emerges as an intervening variable. The study offers insights for the gradual integration of EVs into Indonesia's automotive sector, highlighting initiatives by both manufacturers and the government, such as introducing EV options and implementing regulations related to energy, charging infrastructure, and taxation. This research underscores the importance of addressing consumer perceptions and market dynamics to facilitate the transition toward electric mobility in Indonesia.